Akselerasi Ekonomi Kreatif Masyarakat Desa Barumanis, Kecamatan Bermani Ulu, Kabupaten Rejang Lebong, Bengkulu: Pelatihan Pengolahan Sampah Organik Berbasis Budidaya Maggot (Black Soldier Fly/BSF) - Hadi Wibowo, Risky; Welly Darwis; Helmiyetti; Sipriyadi; Anggun Sasmita; Raul Fadhilon; Rangga Ardiansyah; Uci Cahlia; Riziq Ilham Nurfahmi (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Barumanis Village, located in Bermani Ulu District, Rejang Lebong Regency, Bengkulu Province, has considerable horticultural agricultural potential, particularly in the production of fruits and vegetables. Intensive agricultural activities generate large amounts of organic waste that have not been optimally managed, leading to environmental pollution, unpleasant odors, and the proliferation of disease vectors. One environmentally friendly and economically valuable alternative for managing organic waste is the cultivation of Black Soldier Fly (BSF) larvae (Hermetia illucens). This community service program aimed to enhance the knowledge and practical skills of local residents in utilizing organic waste as a substrate for BSF larvae cultivation, thereby supporting the development of community-based creative economic activities. The program was implemented in three stages: (1) educational outreach on the characteristics, benefits, and cultivation techniques of BSF larvae; (2) demonstrations and hands-on training in organic waste management and BSF cultivation; and (3) evaluation and monitoring using pre-test and post-test instruments. The results demonstrated a significant improvement in participants’ understanding of the benefits of BSF larvae, cultivation techniques, and their potential application as a sustainable solution for organic waste management and an alternative source of household income. Evaluation results indicated that participants who initially had limited knowledge of BSF cultivation showed marked improvement, as reflected by higher post-test scores compared to pre-test scores. This program is expected to encourage the implementation of sustainable organic waste management practices while improving community welfare through the development of BSF cultivation enterprises based on local resources.